Long-Term Follow-Up of Quality of Life following DIEP Flap Breast Reconstruction. Issue 5 (May 2016) - Hunsinger, Vincent; Hivelin, Mikael; Derder, Mohamed; Klein, Delphine; Velten, Michel; Lantieri, Laurent
Abstract : Background: Sequelae resulting from breast cancer negatively impact patients' quality of life. Although the deep inferior epigastric perforator (DIEP) flap has become a standard for autologous breast reconstruction, there are limited data regarding long-term quality of life. The authors studied patients' quality of life more than 5 years after DIEP flap breast reconstruction and compare it with two French reference samples. Methods: A cross-sectional study of quality of life was performed in women who underwent DIEP flap breast reconstruction between 1995 and 2007 using the Medical Outcomes Study 36-Item Health Survey (Short Form-36). The first reference sample included subjects from the French general population ( n = 3308), and the second included cancer survivors who underwent mastectomy with ( n = 70) or without ( n = 135) breast reconstruction. Results: One hundred eleven respondents were analyzed among 186 eligible women. The mean follow-up period after reconstruction was 8.6 years (range, 5 to 15 years). There were no statistically significant differences in the quality of life between women from 45 to 64 years old who underwent DIEP flap breast reconstruction and from the French general population. Five of the eight Short Form-36 dimensions were significantly better in the DIEP flap breast reconstruction group in the 65- to 74-year-old cohort. In addition, quality of life of our study population was significantly higher than that of women who underwent mastectomy with or without any type of breast reconstruction. Conclusion: These results indicate that DIEP flap breast reconstruction allows patients with breast cancer to maintain a good postoperative quality of life comparable to that of the general population. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Video Discussion by Minas Chrysopoulo, M.D., is Available Online for this Article.